EFFECT OF ARTERIAL HYPERTENSION ON LEFT VENTRICULAR GEOMETRIC REMODELING AND LEFT ATRIAL MECHANICAL DYSFUNCTION IN ATRIAL FIBRILLATION - M. Ya. Dotsenko; S. S. Boev; O. V. Molodan; L. V. Gerasimenko; I. O. Shehunova; O. Ya. Malinovska (Сучасні медичні технології, 2022)
Summary. Purpose: to study changes in the structural and functional parameters of the left atrium and left ventricle in patients with arterial hypertension and atrial fibrillation.